Radio quided surgery in thyroid cancer – Intraoperative scintigraphy - Stachlewska-Nasfeter, Elżbieta (Contemporary Oncology/Współczesna Onkologia, 1999)
Taking into consideration the effects of radical surgical treatment of differentiated thyroid cancer in our centre as well as results known from the literature, purposness of intraoperative scintigraphy in this indication has been evaluated. Two groups of patients with differentiated thyroid cancer underwent total thyroidectomy. In a group of 20 patients operated and reoperated without the use of intraoperative scintigraphy mean 131-I uptake over the neck measured 4 weeks postoperatively was 5,9% (range from 0,4% to 23%). In a group of 40 patients operated with a use of intraoperative mean 131-I uptake over the neck measured 4 weeks postoperatively was 1,6% (range from 0% to 3,2%). The results obtained are statistically significant.